Deleterious Effects of an Air Pollutant (NO2) on a Selection of Commensal Skin Bacterial Strains, Potential Contributor to Dysbiosis? - Janvier, Xavier; Alexandre, Stéphane; Boukerb, Amine M.; Souak, Djouhar; Maillot, Olivier; Barreau, Magalie; Gouriou, Frantz; Grillon, Catherine; Feuilloley, Marc G. J.; Groboillot, Anne (Frontiers in Microbiology, 2020)
The skin constitutes with its microbiota the first line of body defense against exogenous stress including air pollution. Especially in urban or sub-urban areas, it is continuously exposed to many environmental pollutants including gaseous nitrogen dioxide (gNO2). Nowadays, it is well established that air pollution has major effects on the human skin, inducing various diseases often associated with microbial dysbiosis. However, very few is known about the impact of pollutants on skin microbiota. In this study, a new approach was adopted, by considering the alteration of the cutaneous microbiota by air pollutants as an indirect action of the harmful molecules on the skin. The effects of gNO2 on this bacterial skin microbiota was investigated using a device developed to mimic the real-life contact of the gNO2 with bacteria on the surface of the skin. Five strains of human skin commensal bacteria were considered, namely Staphylococcus aureus MFP03, Staphylococcus epidermidis MFP04, Staphylococcus capitis MFP08, Pseudomonas fluorescens MFP05, and Corynebacterium tuberculostearicum CIP102622. Bacteria were exposed to high concentration of gNO2 (10 or 80 ppm) over a short period of 2 hours inside a gas exposure device. The physiological, morphological, and molecular responses of the bacteria after the gas exposure were assessed and compared between the different strains and the two gNO2 concentrations. A highly significant deleterious effect of gNO2 was highlighted, particularly for S. capitis MFP08 and C. tuberculostearicum CIP102622, while S. aureus MFP03 seems to be the less sensitive strain. It appeared that the impact of this nitrosative stress differs according to the bacterial species and the gNO2 concentration. Thus the exposition to gNO2 as an air pollutant could cause dysbiosis, which would affect skin homeostasis. The response of the microbiota to the nitrosative stress could be involved in some pathologies such as atopic dermatitis.